2019
DOI: 10.1007/s00376-018-8100-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of South China Sea Summer Monsoon Onset

Abstract: Predicting monsoon onset is crucial for agriculture and socioeconomic planning in countries where millions rely on the timely arrival of monsoon rains for their livelihoods. In this study we demonstrate useful skill in predicting year to year variations in South China Sea summer monsoon onset at up to 3 months lead time using the GloSea5 seasonal forecasting system. The main source of predictability comes from skilful prediction of Pacific sea surface temperatures associated with El Niño and La Niña. The South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…However, as noted by Wang et al (2008), an advantage of the EASMI is that it can be monitored on a variety of time scales and is known to be an excellent indicator of variations in the SCS summer monsoon onset (Wang et al, 2004). Martin et al (2019) recently demonstrated significant predictive skill for the SCS summer monsoon onset in GloSea5. We next investigate the predictive skill for the monthly mean EASMI in GloSea5.…”
Section: Sources Of Skillmentioning
confidence: 99%
“…However, as noted by Wang et al (2008), an advantage of the EASMI is that it can be monitored on a variety of time scales and is known to be an excellent indicator of variations in the SCS summer monsoon onset (Wang et al, 2004). Martin et al (2019) recently demonstrated significant predictive skill for the SCS summer monsoon onset in GloSea5. We next investigate the predictive skill for the monthly mean EASMI in GloSea5.…”
Section: Sources Of Skillmentioning
confidence: 99%
“…() and National Climate Center (). Since the zonal wind is the most prominent parameter of the SCSSM and is widely used in determining the SCSSM onset (e.g., Wang et al ., ; Kajikawa and Wang, ; Luo and Lin, ; Hu et al ., ), thus the zonal wind is also employed to determining the SCSSM withdrawal day in this study as in previous studies (Luo and Lin, ; Hu et al ., ; ; ; Martin et al ., ). Namely, the monsoon withdrawal is regarded as the nearest day to the withdrawal pentad of National Climate Center () when the westerly to easterly transition occurs.…”
Section: Methodsmentioning
confidence: 99%
“…One may argue that the SCSSM withdrawal date determined by National Climate Center (2016) is somewhat subjective (e.g., "steadily" transition and the large-scale circulation pattern), and it may be more reasonable to objectively determine the monsoon withdrawal by some criteria (e.g., Lam et al, 2005;Zhang et al, 2014;Luo and Lin, 2017). By considering the same two monsoonal parameters (but the threshold for potential pseudo-equivalent temperature is set to 335 K; Martin et al, 2019), Zhang et al (2014) quantitatively defined the steadily state as (a) the state is maintained for two pentads and is then interrupted for one pentad but immediately returns to the state before interruption, or (b) the state is maintained at least for three pentads and can be interrupted for no more than two pentads thereafter. Most of the SCSSM withdrawal pentad determined by National Climate Center (2016) and Zhang et al (2014) are the same, and their correlation is as high as 0.74 during 1951-2102, which is significant at the 99.9% confidence level according to the two-tailed Student's t test (Hu et al, 2018b).…”
Section: Methodsmentioning
confidence: 99%
“…While the South Asian monsoon is confined to be equatorward of ∼ 30 • N, the East Asian monsoon extends north of this into the extratropics. Although the monsoon onset over the South China Sea has been considered a precursor to the East Asian monsoon onset (Martin et al, 2019;B. Wang et al, 2004), some authors (e.g., B.…”
Section: East Asian 'Monsoon'mentioning
confidence: 99%